Interrelations Between Arterial Stiffness, Target Organ Damage, and Cardiovascular Disease Outcomes - Vasan, Ramachandran S.; Short, Meghan I.; Niiranen, Teemu J.; Xanthakis, Vanessa; DeCarli, Charles; Cheng, Susan; Seshadri, Sudha; Mitchell, Gary F. (Journal of the American Heart Association, 2019)
Background Excess transmission of pressure pulsatility caused by increased arterial stiffness may incur microcirculatory damage in end organs (target organ damage [TOD] ) and, in turn, elevate risk for cardiovascular disease ( CVD ) events. Methods and Results We related arterial stiffness measures (carotid-femoral pulse wave velocity, mean arterial pressure, central pulse pressure) to the prevalence and incidence of TOD (defined as albuminuria and/or echocardiographic left ventricular hypertrophy) in up to 6203 Framingham Study participants (mean age 50±15 years, 54% women). We then related presence of TOD to incident CVD in multivariable Cox regression models without and with adjustment for arterial stiffness measures. Cross-sectionally, greater arterial stiffness was associated with a higher prevalence of TOD (adjusted odds ratios ranging from 1.23 to 1.54 per SD increment in arterial stiffness measure, P<0.01). Prospectively, increased carotid-femoral pulse wave velocity was associated with incident albuminuria (odds ratio per SD 1.28, 95% CI, 1.02-1.61; P<0.05), whereas higher mean arterial pressure and central pulse pressure were associated with incident left ventricular hypertrophy (odds ratio per SD 1.37 and 1.45, respectively; P<0.01). On follow-up, 297 of 5803 participants experienced a first CVD event. Presence of TOD was associated with a 33% greater hazard of incident CVD (95% CI , 0-77%; P<0.05), which was attenuated upon adjustment for baseline arterial stiffness measures by 5-21%. Conclusions Elevated arterial stiffness is associated with presence of TOD and may partially mediate the relations of TOD with incident CVD . Our observations in a large community-based sample suggest that mitigating arterial stiffness may lower the burden of TOD and, in turn, clinical CVD .